As representações sociais de famílias de adolescentes envolvidos em bullying: características e percepções do fenômeno - Soraia Pinto Sena (2013)
Bullying is a specific type of aggressive behavior that occurs mostly in school among peers. This behavior many times occurs disguised under the argument as a simple joke, not being sometimes taken seriously by adults. In this research the phenomenon bullying was studied under a different approach: the family perspective. It represented a challenge. It is worth noting at this point, the sociological dimension of the phenomenon. The aim of the study was to identify and understand what the social representations of the different families of adolescents involved in bullying on the phenomenon are having their own perceptions as the starting point. The specific objectives were: to identify the parents concept on bullying; to analyze the parents attitudes towards the situations experienced by adolescents; to identify and analyze the type of parents-child relationships; to identify the impact of bullying on adolescents; to identify and analyze the reports on the school attitude regarding bullying. The methodology used was qualitative. Two instruments used were focus group and semi-structured interview. The study comprised 36 families of students of the third cycle of the elementary school (7th, 8th and 9th grades) from a Municipal Public School in the center-south area of Belo Horizonte. For data organization it was used the Collective Subject Discourse (CSD) methodology, which presents an interface with the Social Representation Theory, method used for findings analysis. Five themes were found from the Collective Subject Discourse (CSD): the parents concept on bullying; the parents attitudes towards the experiences lived by adolescents; the types of parent-child relationships; the impacts of bullying on adolescents; schools attitudes before bullying. To know how these families are interpreting this phenomenon and how they deal with on daily basis became a priority not only in the field of Education but also in the field of Health. All the motivation underlying this work was to know the positions of the families of adolescents involved in bullying as an aggressor, a victim, or an observer, since long it has been known that among the prevention measures to avoid aggressive behaviors in the school context, the family involvement is indispensable.